Subtract C in both sides:
2c + 1 = 1
Subtract 1 on both sides
2c = 0
The solution is:
x = 0
Hope this helped
Answer:
I don't know what you are trying to say but I will take the points.
Answer:
f(x+2) = 3(x+2)^2 + 2(x+2 + 1
Step-by-step explanation:
you need to replace the x with x+2
Answer:
C. 8^x/3
Step-by-step explanation:
According to algebraic principles, if n is the root of a number, then that number to the power of 1/n is equal to it. This would mean that n√a = a^1/n.
This would mean that 3√8 = 8^1/3. When there is a power added to a radical expression such as this, that power will go on the denominator. So (3√8)^2 for example is equal to 8^2/3, and in your case, (3√8)^x = 8^x/3
looking back on the fact that this was added 2 days ago i dont think this helped on your quiz
The T-shirt launcher can launch 315 shirts per hour.